Maternal PM10 Exposure Increases Risk for Spina Bifida: A Population-Based Case-Control Study - Li, Huan; Huang, Yan-Hong; Li, Jing; Liu, Shu; Chen, Yan-Ling; Li, Li-Li; Jiang, Cheng-Zhi; Chen, Zong-Jiao; Li, Na (Frontiers in Public Health, 2021)
Limited studies have focused on the impact of ambient air pollution on spina bifida. A population-based case-control study was conducted in Liaoning Province, China to assess the associations between maternal PM10 exposures in various exposure windows and spina bifida risk. Data on spina bifida cases born between 2010 and 2015 were available from the Maternal and Child Health Certificate Registry of Liaoning Province. Controls were a random sample of healthy livebirths without any birth defects delivered in the selected five cities during 2010-2015. Ambient air monitoring data for PM10 were obtained from 75 monitoring stations in Liaoning Province. The multivariable logistic regression models were established to calculate adjusted odds ratios (OR) and 95% confidence intervals (CI). We further performed sensitivity analyses by using three propensity score methods. A total of 749 spina bifida cases and 7,950 controls were included. After adjusting for potential confounders, spina bifida was associated with a 10 μg/m3 increment in PM10 during the first trimester of pregnancy (adjusted OR = 1.06, 95%CI: 1.00-1.12) and the three months before pregnancy (adjusted OR = 1.12, 95%CI: 1.06-1.19). The adjusted ORs in the final model for the highest vs the lowest quartile were 1.51 (95% CI: 1.04-2.19) for PM10 during the first trimester of pregnancy and 2.01 (95% CI: 1.43-2.81) for PM10 during the three months before pregnancy. Positive associations were found between PM10 exposures during the single month exposure windows and spina bifida. Sensitivity analyses based on two propensity score methods largely reported similar positive associations. Our findings support the evidence that maternal PM10 exposure increases the risk of spina bifida in offspring. Further validation with a prospective design and a more accurate exposure assessment is warranted.